Zn–Fe alloy electrodeposition from chloride bath: Influence of deposition parameters on coatings morphology and structure. Issue 4 (10th October 2011) - Amirat, S.; Rehamnia, R.; Bordes, M.; Creus, J.
Abstract In this study, the kinetics of Zn–Fe codeposition was investigated in chloride acidic solution using cyclic voltammetry. Anomalous codeposition is detected and this mechanism depends on the Zn(II)/Fe(II) concentration ratio in the electrolytic bath. Influence of deposition parameters on the morphology and structure of the coatings is discussed using characterization techniques and using the anodic linear sweep voltametry (ALSV). The ratio between Zn(II)/Fe(II) considerably influences the structure of the alloys. Dense, uniform, and single‐phased Zn–Fe coatings could be obtained.